ADSORBENT AND ITS MANUFACTURING METHOD - BABA YOSHINARI (2007)
PROBLEM TO BE SOLVED: To provide an adsorbent having a high selectivity, a high absorption capacity, and a high absorption rate, and its manufacturing method. SOLUTION: The adsorbent wherein chitosan derivatives are used as a raw material contains a resin having a recognition site of a mold material such as a metal ion formed by a molecular imprinting method. The manufacturing method of the adsorbent comprises the steps of forming a complex by a contact of the chitosan derivatives with the mold material, thereafter, of carrying out a crosslink by adding a cross-linker, and then, of removing the mold material. COPYRIGHT: (C)2007,JPO&INPIT